Outcome after resection of breast cancer liver metastases - Bockhorn, Maximilian; Frilling, Andrea; Busche, Caroline; Fingas, Christian; Molmeti, Ernesto; Broelsch, Christoph E (International Journal of Hepatology, 2010)
Background: Goal of our study was to evaluate the outcome of patients who underwent hepatic resection as part of a multimodality-treatment. Methods: 38 female patients with a median age of 55.2 years underwent hepatic resection with curative intent from 1998-2006. The liver was the only site of metastatic disease. Results: 15 patients underwent major (>3segments), 11 patients minor hepatic resections, and 12 were only explored. Median hospital stay was 14.6 days, with a postoperative morbidity of 7%, and a 30-day mortality of 7%. One-, 3-, and 5-year survival among resected patients was 88%, 53% and 44%, respectively. The corresponding disease free survival was 48%, 8%, and 8%. There was no association between treatment- or patient-specific variables and survival. Conclusions: Resection seems to benefit a cohort of patients with breast cancer International Journal of Hepatology Vol.1(3) 2010 pp.39-43